2019
DOI: 10.1002/ijc.32264
|View full text |Cite
|
Sign up to set email alerts
|

Statins and pancreatic cancer risk in patients with chronic pancreatitis: A Danish nationwide population‐based cohort study

Abstract: Statins (HMG‐CoA reductase inhibitors) have antiinflammatory and possibly anticancer properties. We hypothesized that statin use is associated with lower risk of pancreatic cancer in patients with chronic pancreatitis. This nationwide population‐based cohort study included all Danish patients diagnosed with incident chronic pancreatitis from 1 January 1996 to 31 December 2012. We used the Danish National Prescription Registry to ascertain information on statin prescriptions for members of the study population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Statin use significantly decreased the risk of pancreatic cancer in nearly 50% in patients with type 2 DM, 47 but that for patients with CP was not clear because two previous studies reported inconsistent conclusions. 48,49 Meanwhile, a nearly 30% lower risk for pancreatic cancer with regular aspirin use among participants with DM was observed in a large cohort study, 20 which was similar to result of this study, but it does not appear to be affected by the cumulative dose of aspirin use. Few studies have been conducted on the relationship between aspirin use and PDAC for patients with risk factors, and it is necessary to further evaluate in the future.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Statin use significantly decreased the risk of pancreatic cancer in nearly 50% in patients with type 2 DM, 47 but that for patients with CP was not clear because two previous studies reported inconsistent conclusions. 48,49 Meanwhile, a nearly 30% lower risk for pancreatic cancer with regular aspirin use among participants with DM was observed in a large cohort study, 20 which was similar to result of this study, but it does not appear to be affected by the cumulative dose of aspirin use. Few studies have been conducted on the relationship between aspirin use and PDAC for patients with risk factors, and it is necessary to further evaluate in the future.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, well‐designed studies with a large number of patients have reported the relationship between statin use and PDAC in high risk patients with DM or CP. Statin use significantly decreased the risk of pancreatic cancer in nearly 50% in patients with type 2 DM, but that for patients with CP was not clear because two previous studies reported inconsistent conclusions . Meanwhile, a nearly 30% lower risk for pancreatic cancer with regular aspirin use among participants with DM was observed in a large cohort study, which was similar to result of this study, but it does not appear to be affected by the cumulative dose of aspirin use.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Dear Sir, We read with great interest the recently published study on the association between statins and pancreatic cancer risk in patients with chronic pancreatitis (CP). 1 Preventing the progression from CP to pancreatic cancer is of great significance. Statins are widely used as cholesterol-lowering drugs nowadays.…”
mentioning
confidence: 99%
“…Dear Sir, We thank Liu et al for their interest in our recent study in International Journal of Cancer on statins and pancreatic cancer risk in patients with chronic pancreatitis. 1 Liu et al raises concern about some potential flaws in our study design, to which we would like to reply.…”
mentioning
confidence: 94%